PROGRAM PENYALURAN BERAS MISKIN DI KECAMATAN SIAK HULU KABUPATEN KAMPAR TAHUN 2015-2016 - Fadhillah, M. Arif; M, Erman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
One of the poverty alleviation programs carried out by the government is to provide assistance in the form of basic needs of rice to poor households so that this is expected to reduce poverty in the region. The implementation of the poor rice distribution program is carried out one of them in the Siak Hulu District of Kampar Regency with the target of poor households with an economic category of poor households.This research uses descriptive qualit   ative method by describing the current state of the subject and object of research based on the facts that occur. The research location is in Siak Hulu Subdistrict, Kampar Regency and the writer collected research data from interviews with research informants as well as documentation of books, government regulations, journals, mass media several internet media sites.This research concludes that the implementation of the poor rice distribution program (Raskin) in Siak Hulu District, Kampar Regency was carried out in accordance with government regulations ranging from district level distribution to the point of ransom. Several factors that hampered the implementation of the poor rice distribution program (Raskin) in Siak Hulu Subdistrict, Kampar Regency were the lack of communication and socialization among the implementation team, the low quality of implementing resources, the attitude of program implementers who were not serious and the absence of clear operational standards in the distribution raskin in Siak Hulu District so that the price sold does not match the price of the redemption point.Keywords:  implementations, program and rice poor.